Growth and production of M6 and M7 black soybean mutant genotypes - SYAIFUL ANWAR; FLORENTINA KUSMIYATI; DWI RETNO LUKIWATI; MUHAMAD GHAZI AGAM SAS; YULIA NUR ARIFAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Anwar S, Kusmiyati F, Lukiwati DR, Sas MGA, Arifah YN. 2024. Growth and production of M6 and M7 black soybean mutant genotypes. Biodiversitas 25: 2541-2546. The seed coat colors of soybeans are yellow, black, green, brown, or bicolor, and in Indonesia, black seed coat color is for used soy sauce. Our black soybean mutation breeding research started with irradiating soybean cultivar Detam 3 with gamma rays at 160, 208, 256, 304, 352, 400, 448, 496, 544, and 592 Gy. Genotypes were selected from M1 (first generation) to M5 (fifth generation) based on saline and/or nonsaline soil productions. This research aims to evaluate the growth and production of sixth-generation (M6) and seven-generation (M7) black soybean mutant genotypes. The research was conducted in Karangharjo Village, Pulokulon Sub-district, Grobogan District, Central Java Province, Indonesia. The plant material was three genotypes of M6 black soybean mutants (BSMG VQ 05-256/1-6-2-28, BSMG VQ 05-400/1-2-2-6 and BSMG VQ 05-256/1-2-9-29), four genotypes of M7 black soybean mutants (BSMG VQ 06-256/1-6-2-28, BSMG VQ 06-400/1-2-2-6 and BSMG VQ 06-256/1-2-9-29 and BSMG VQ 06-256/1-4-2-21) and three cultivar checks (Detam 1, Detam 3/parent variety and Detam 4 variety). The parameters measured consist of plant growth, components, and production. All data collected were subjected to statistical Analysis of Variance (ANOVA); if significantly different, it continued by Duncan Multiple Range Test (DMRT). The results showed that the genotype treatment affected all observed characters except plant height. Selected lines based on the number of leaves, number of pods, number of seeds, weight of 100 seeds, weight of seed, and production were BSMG VQ 05-256/1-2-9-29, BSMG VQ 05-256/1-2-9-29 and BSMG VQ 06-256/1-4-2-21. These selected genotypes provided the prospective source of soy sauce material and needed to examine its stability at different locations (multilocation test).